Evaluation of PT Petrokimia Gresik's LONTAR Program With SROI (Social Return On Investment) - Aulya, Aulya Mauizzati; Haryanti, Agustin Dwi (Dinasti Publisher, 2025)
This study evaluates the LONTAR Program (Kelompok Jajanan Masyarakat Sekitar) by PT Petrokimia Gresik in 2023 using the Social Return On Investment (SROI) method. This program aims to empower MSMEs through skills training and free bazaar facilities. SROI analysis is carried out using the Present Value, Future Value, and Real Value approaches to measure social, economic, and environmental impacts. The results show SROI values of 2.20 (Present Value), 2.07 (Future Value), and 2.08 (Real Value), which means that every investment of IDR 1.00 generates a social return of IDR 2.20, IDR 2.07, and IDR 2.08. These findings indicate a positive and sustainable impact, especially in increasing the income and skills of MSMEs. The study recommends scaling up programs and ongoing training to maximize their impact, while encouraging the adoption of SROI methods in the evaluation of corporate social responsibility programs.